High efficacy therapy to prevent the formation of meningeal tertiary lymphoid organs after CXCL13 index screening in early multiple sclerosis - Londoño, Ana C.; Mora, Carlos A. (Frontiers in Neuroscience, 2025)
Postmortem studies have shown the presence of subpial inflammation with tertiary lymphoid organs (TLO) in the meninges of patients with progressive multiple sclerosis, playing an important role in the pathophysiology of the disease. The chemokine (C-X-C motif) ligand 13 (CXCL13) induces the formation of these lymphoid organs, thus promoting activity of disease. The progression to disability in multiple sclerosis has been reduced, thanks to the effect of disease modifying therapy. However, despite advances in the treatment of disease with immunomodulatory agents, we still lack specific laboratory biomarkers that could indicate the state of activity of disease, either at time of diagnosis or when escalation therapy seems to be mandatory. In patients with multiple sclerosis, MRI studies have not demonstrated the presence of TLO in the CNS, so far. The determination of the CXCL13 index (ICXCL 13), in clinical specimens, could become a reliable biomarker for the verification of the presence and activity of the TLO, thus contributing to improving therapy outcome, with high efficacy therapy, in the clinical setting.